Sonographic Septation: A useful Diagnostic Predictor of Complicated Parapneumonic Effusion. (December 2021) - Chang, Shan-Yueh; Chen, Ying-Chieh; Tsai, Chen-Liang; Wu, Shih-Wei; Peng, Chung-Kan; Shen, Chih-Hao; Chou, Yu-Ching; Chian, Chih-Feng
Sonographic septation is associated with prolonged hospitalization and increased mortality in patients diagnosed with empyema. However, it is unknown whether sonographic septation is associated with complicated parapneumonic effusion (CPPE) or the need for invasive procedures among patients with pneumonia. In this retrospective study, we included 180 patients with non-purulent neutrophilic exudative pleural effusion secondary to pulmonary infections such as pneumonia and lung abscess. We performed univariate and multivariate logistic regression analyses, including baseline clinical characteristics, values from blood samples, and sonographic echogenicity, to identify variables correlated with CPPE and the need for invasive procedures. Seventy of the 180 included patients (38.89%) displayed sonographic septation. Multivariate logistic regression analysis identified that sonographic septation (adjusted OR (AOR)=3.38 (95% CI 1.64 to 6.98), p=0.001) and younger age (AOR=2.63 (95% CI 1.24 to 5.58), p=0.012) were independently associated with CPPE. With regard to treatment strategy, sonographic septation (AOR 9.06 (95% CI 3.71 to 22.11), p<0.001) and total serum protein level (AOR=1.80 (95% CI 1.13 to 2.86), p=0.013) were independently associated with the need for subsequent invasive procedures in patients with CPPE using multivariate logistic regression analysis. Sonographic septation is a useful predictor of CPPE and may imply the need for early invasive procedures.